One Country, Three Norms The Phenomenon of Interfaith Marriage among the Sakai Tribe in Penyengat Village, Sungai Apit District, Siak Regency - Samah, Abu; Kurniawan, Roni (Jurnal Ushuluddin, 2025)
The purpose of this study was to examine the phenomenon of interfaith marriage within the Sakai community of Penyengat Village, Sungai Apit District, Siak Regency. The study focused on its relation to marriage law norms, state administrative law norms, the fulfillment of human rights, and Islamic legal principles. This research employed a normative-empirical method with a qualitative descriptive approach, utilizing interviews with traditional leaders and interfaith couples. The results of this study indicate that: (1) the phenomenon of interfaith marriage in the Penyengat community of Penyengat Village does not conflict with the Marriage Law, specifically Article 2, paragraph (1), which states that a marriage is valid if conducted according to the laws of each religion and belief, as outlined in statutory provisions or unless otherwise specified by law; (2) according to population administration law, such marriages are also valid because they do not conflict with Article 2 of Law No. 23 of 2006 concerning Population Administration, which guarantees every resident the right to: (a) obtain population documents; (b) receive equal services in population and civil registration; (c) protection of personal data; and (d) legal certainty regarding document ownership. Furthermore, under human rights law, these marriages are valid as they do not conflict with Law Number 39 of 1999 concerning Human Rights. Article 10, paragraph 1, states that everyone has the right to form a family and continue their lineage through a legal marriage, and paragraph 2 specifies that a legal marriage can only occur based on the free will of the prospective husband and wife in accordance with applicable laws and regulations; (3) according to Islamic legal norms, the phenomenon of interfaith marriage in the Penyengat Village community, Penyengat District, Sungai Apit Regency, Siak Regency, is considered invalid or haram because: (a) it is prohibited by Surah Al-Baqarah verse 221, Surah Al-Mumtahanah verse 10, and Surah Al-Maidah verse 5; (b) the couple has stated that after remarrying, they practice their respective religions; (c) marriage is not solely a biological relationship but also involves psychological (influence on thoughts and mentality), sociological (social environment), and theological (divine values) aspects. Therefore, the husband has responsibilities toward his wife, children, society, and Allah SWT, with the aim of achieving peace; and (d) such marriages can harm religion, the soul, reason, and descendants, and they generate both support and opposition within society